The Potential Role of MicroRNA‐124‐3p in Growth, Development, and Reproduction of Schistosoma japonicum - Zhou, Xue; Hong, Yang; Shang, Zheng; Abuzeid, Asmaa M. I.; Lin, Jiaojiao; Li, Guoqing (Frontiers in Cellular and Infection Microbiology, 2022)
The microRNA‐124‐3p plays an important role in regulating development and neurogenesis. Previous microRNA sequencing analyses of Schistosoma japonicum revealed sja-miR-124-3p differential expression patterns in schistosomes from different hosts and at different developmental stages. This study explores the regulatory role of sja-miR-124-3p in S. japonicum development and reproduction. Quantitative reverse-transcription PCR (qRT-PCR) showed that the expression level of sja-miR-124-3p in S. japonicum from resistant hosts, such as Microtus fortis, and unsuitable hosts, such as rats and water buffalo, was significantly higher than that in mice and yellow cattle at the same developmental stage. Overexpressing sja-miR-124-3p in infected mice led to a hepatic egg reduction rate of 36.97%, smaller egg granulomas in the livers, increased liver weight, subsided hepatocyte necrosis, and diminished inflammatory cell infiltration. The width of female worms increased but decreased in males. The vitelline cells were irregular, swollen, or fused. The teguments and ventral sucker of males and females were swollen and broken, but the morphological changes were particularly notable in males. qRT-PCR and dual-luciferase reporter assay system were used to confirm the in-silico-predicted target genes, S. japonicum DEAD-box ATP-dependent RNA helicase 1 (sjDDX1) and DNA polymerase II subunit 2 (sjPOLE2). Our results showed that RNA interference (RNAi)-mediated sjDDX1 silencing in mice provided a 24.55% worm reduction rate and an 18.36% egg reduction rate, but the difference was not significant (p > 0.05). Thus, our findings suggest that sja-miR-124-3p has an important role in growth, development, and reproduction in S. japonicum. All these results will greatly contribute toward providing important clues for searching vaccine candidates and new drug targets against schistosomiasis.